The Interaction Effects of Age and Body Size on Body Appreciation and Health-Related Behaviors - Minsun Lee; Hyun-Hwa Lee (International Journal of Psychological Research, 2022)
Whilst the associations among age, body size, body (dis)satisfaction, and weight management behavior have been well documented, there is little research on how the combination of age and body size is related to body appreciation and health-related behavioral intentions. The purpose of this study is to identify the associations of age, body size, and their interactions with body appreciation and health-related behavioral intentions among Korean women. A cross-sectional research design was adopted with a convenience sampling method. Using an online survey questionnaire, complete data on body appreciation, health-related behavioral intentions, body size, height, weight, and age were collected from 531 Korean adult women aged 20-77 years. Using average scores for each variable, a series of hierarchical regression analyses were performed to identify the relative contributions of predictor variables on each criterion variable. The significant interaction terms were further examined using the PROCESS macro in SPSS. Overall, older Korean women were found to be more likely to have a positive body image and lower levels of behavioral intentions towards striving for a healthy body than younger women. This study confirmed the relative contribution of subjective body size in explaining women’s body-related perceptions and behaviors, as compared to their actual BMI.